Development of Simple, Precise UV Spectroscopic Method for the Estimation of Escitalopram Oxalate in Bulk and Marketed Tablets - Polkal, Pooja; Srinivasulu, Neeladri; Anand Kumar, Yegnoor; Shetty, Keerthana; Madusri, Chagi (Asian Journal of Pharmaceutical Research and Development, 2024)
Two new simple and accurate solvent mediums have been presented for the quantification of Escitalopram Oxalate (ESC) in tablet dosage form. A linear relationship found in the concentration range of 1-24 µg/ml for two proposed mediums viz., phosphate buffer pH 7.4 (Medium 1) and methanol: phosphate buffer pH 7.4 [1:1](Medium 2).The goodness of fit study suggests good correlation coefficient (R2 - 0.9998 and 0.9998 for proposed mediums) shows the validity of Beer’s law with intercept response < 2% calculated by the least square method indicating functional linearity between the concentration of analyte and the absorbance. Based on standard deviation of the response and slope, the LOD values for ESC for the proposed mediums found to be 0.348±0.00238 μg/ml, 0.273±0.0014 μg/ml and LOQ values found to be 1.046±0.002458 μg/ml, 0.823±0.00065 μg/ml with % RSD values less than 2.The proposed methods were successfully applied to the determination of commercially available tablets with a high percentage of recovery, good accuracy and precision.